Broadening of the spectra of femtosecond laser pulses upon passing through optical materials; Bulletin of the Russian Academy of Sciences: Physics; Vol. 79, № 2 - Alekseev S. V. Sergey Vladimirovich; Ivanov N. G. Nikolay Georgievich; Ivanov M. V. Mikhail Valerjevich; Losev V. F. Valery Fedorovich; Panchenko Yu. N. Yury Nikolaevich (2015, 2015)
Title screen